1978
DOI: 10.1084/jem.148.1.207
|View full text |Cite
|
Sign up to set email alerts
|

Human C4-binding protein. I. Isolation and characterization

Abstract: Human C4 and mouse Ss proteins show extensive structural homologies. They are antigenically related (1) and are composed of three polypeptide chains of similar molecular weights, linked by disulfide bonds (2, 3). In addition, it is very likely that the major histocompatibility complex of these species contains structural genes for beth proteins (3-5). However, some functional differences between the Ss protein and the C4 hemolytic activity of mouse serum have been reported (6).We recently described a new prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
146
0
2

Year Published

1984
1984
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(151 citation statements)
references
References 22 publications
3
146
0
2
Order By: Relevance
“…First, we tested whether C4BP purified from plasma consisting of seven ␣-chains and one ␤-chain will bind pili with the same apparent affinity as the recombinant C4BP that is composed exclusively of ␣-chains. ␣-Chains are known to bind C4b (17), heparin (41), Bordetella pertussis (24), Streptococcus pyogenes (23), and serum amyloid P component (42), whereas ␤-chain binds anticoagulant protein S (18). We found that both forms of C4BP bound to pili with similar affinities, implying that ␣-chains confer the ability to bind gonococcal pili.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we tested whether C4BP purified from plasma consisting of seven ␣-chains and one ␤-chain will bind pili with the same apparent affinity as the recombinant C4BP that is composed exclusively of ␣-chains. ␣-Chains are known to bind C4b (17), heparin (41), Bordetella pertussis (24), Streptococcus pyogenes (23), and serum amyloid P component (42), whereas ␤-chain binds anticoagulant protein S (18). We found that both forms of C4BP bound to pili with similar affinities, implying that ␣-chains confer the ability to bind gonococcal pili.…”
Section: Discussionmentioning
confidence: 99%
“…They are present mainly, but not exclusively, in proteins involved in the activation and regulation of the complement system. One of these regulators is C4BP, a large plasma protein consisting of seven identical ␣-chains and one ␤-chain held together by disulfide bonds (17,18). The ␣-and ␤-chains consist of eight and three CCP domains, respectively, and have C-terminal domains involved in the polymerization of the molecule (19).…”
mentioning
confidence: 99%
“…The predominant isoform of C4BP has seven ␣-chains each containing eight complement control protein (CCP) modules (or short consensus repeats) and a single ␤-chain with three CCP modules (22,23). Transmission electron microscopy indicated that up to six molecules of C4b bind to one molecule of C4BP at the distal (N-terminal) ends of the seven ␣-chains (2).…”
mentioning
confidence: 99%
“…C4BP is a large protein (570 kDa) consisting of several polypeptides: seven identical ␣-chains and one ␤-chain (4,5). As shown by electron microscopy and biochemical studies, C4BP consists of a ϳ160-kDa central core that can be released by chymotrypsin treatment and several extended tentacles formed by the ␣-chains (6, 7).…”
mentioning
confidence: 99%